Economic Analysis of Nepal's Furniture Industry: Consumer Preferences, Competitive Strategies, and Post-Pandemic Recovery - Lamichhane, Bhubaneshwar (Academia Research Journal, 2025)
Using a mixed methods approach, including consumer surveys, executive interviews, and financial analysis, this study examines Nepal's furniture sector in depth, concentrating on its recovery and transformation following the COVID-19 pandemic. New Structural Economics and behavioural theories are used to investigate changing market dynamics. Along with price sensitivity, essential results show that consumer preferences have increasingly come to be determined by delivery speed and ecocertification. As seen in a new Sustainability–Competitiveness Matrix, companies have responded by adopting local sourcing, increasing automation, and diversifying their competitive strategies. Policy analysis recognizes the need for a graduated response that blends near-term liquidity assurances, medium-term technical advancements, and long-term export assistance. Through the integration of structural impediments and behavioural knowledge, the entire plan is executed to achieve sustainable growth and industry resilience. The consequences have an impact on politicians, business stakeholders, and academics who are interested in the opportunities and challenges that small-scale manufacturing in developing nations presents.